Active noise reduction system - Wojciech CIESIELKA (Archives of Acoustics)
In this article, active noise reduction system has been described. The ANR system was made on basis of finite impulse response filter and realised algorithms LMS or NLMS. The algorithms were implemented on the dSPACE card with floating-point processor TMS320C31. Researches were performed in the anechoic chamber and in the enclosure of dimension 4.4 x 3.05 x 3.2 m and reverberation time T=0.53 s. White noise filtered by third and octave filter with mid-band frequency 125 Hz was used for the experiments. The ANR system working in free field conditions (in the anechoic chamber) allowed to obtain the average acoustic pressure level reduction ranging from 9.1 to 24.1 dB for octave, and 14.7 to 23.1 dB for third octave. Measurements carried out in natural acoustics conditions in a selected room allowed to obtain the following values of average acoustic pressure level reduction: for octave from 2.2 to 14.2 dB, and for third octave from 6.4 to 19.8 dB. The result of experiments proved that the convergence time of NLMS algorithm was several times shorter than convergence time of LMS algorithm.